Les femmes et les olympismes alternatifs durant l’entre-deux-guerres - Clément Dumas (Genre & Histoire)
This article proposes a comparative analysis of the place of women in alternative Olympisms during the inter-war period. Jewish, workers’ and women’s sports movements shared a common opposition to the IOC and they organized sports competitions inspired by the Olympic Games in order to make political and social demands. While Maccabi and workers’ organisations were the bearers of emancipatory projects for Jews and workers, these two movements were marked by conservatism when it came to women’s sport. However, their competitions left sizeable room for women’s events, with programmes that were fairly similar to the women’s games, while taking care to respect the codes of femininity. By looking at women as actors in alternative games, the comparative approach shows that the organization and management of the games are much more feminized in women’s Olympiads, while the figure of the champion is highlighted to illustrate the vitality of alternative Olympisms.